An improved composite current collector and a method for controlling its surface roughness

By etching linear grooves on the metal layer surface of the composite fluid collector, the problem of low surface roughness of the traditional composite fluid collector is solved, significantly improving the adhesion and conductivity of the battery pole sheet, and enhancing the cyclic stability and overall performance of the battery.

CN119764462APending Publication Date: 2025-04-04ALLMATE TECH (HUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963190.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The surface roughness of the composite fluid collector in traditional lithium-ion batteries is low, which leads to easy leakage of electrode slurry, low adhesion and small conductive channels, which affect the adhesion, conductivity and cycle stability of the battery.

Method used

By etching wired grooves on the surface of the metal layer, laser etching method is used to improve control accuracy and reduce damage, and the surface roughness of the composite fluid collection is optimized.

Benefits of technology

It significantly improves the adhesion, conductivity and cycle stability of the battery pole sheet, thereby enhancing the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764462A_ABST
    Figure CN119764462A_ABST
Patent Text Reader

Abstract

The present invention provides an improved composite current collector and a method for controlling its surface roughness. The improved composite current collector can optimize the surface roughness of the composite current collector by etching linear grooves on the surface of a metal layer, significantly improve the adhesion, conductivity and cycle stability of a battery pole piece, and thus enhance the overall performance of the battery. The surface roughness control method of the present invention uses a laser etching method to form linear grooves on a metal surface, which can improve control accuracy, reduce damage to the composite current collector, and is beneficial to improving the performance of the electrode pole piece, thereby improving the performance of a lithium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery current collectors, and in particular to an improved composite current collector and a method for controlling the surface roughness thereof. Background Art

[0002] The current collector is one of the important components of lithium-ion capacitors. The current collector not only carries the electrode active material, but also collects the current generated by the electrode active material to form a larger current output, thereby improving the charging / discharging efficiency of lithium-ion capacitors. Commonly used current collector materials include metal conductor materials such as copper, aluminum, nickel, stainless steel, semiconductor materials such as carbon, and composite materials. Among them, current collectors made of copper and aluminum are more widely used.

[0003] The negative electrode current collector of traditional lithium-ion batteries is copper foil, and the positive electrode current collector is aluminum foil. With the development of lithium battery technology, the high energy density, lightweight and flexibility of lithium-ion batteries have become people's pursuit. Thinning copper / aluminum foil (the total mass of the positive and negative electrode current collectors accounts for about 14%-18% of the total mass of the battery) can achieve the lightweight of lithium-ion batteries, improve energy density and reduce costs, but due to the limitations of preparation technology, the thickness of copper / aluminum foil is difficult to reduce (currently copper foil can be mass-produced to 6μm, and aluminum foil can be mass-produced to 8μm); in addition, after the copper / aluminum foil is thinned, the mechanical strength is reduced, resulting in reduced processing performance. Therefore, it is necessary to develop new "thinning technology", and the research on composite current collectors came into being.

[0004] Composite current collectors are generally made by plating a copper / aluminum metal layer on a plastic layer, such as a copper / aluminum metal layer on a PET layer, to increase battery energy density, reduce costs, and make the battery lighter. The metal layer on the surface of the composite current collector (such as a copper / aluminum metal layer, etc.) is often relatively flat and smooth, with low surface roughness, low surface energy, and low specific surface area, which leads to some problems when coating the electrode slurry, such as: (1) The electrode slurry is easy to leak, which reduces product quality and limits the coating speed; (2) Due to the low specific surface area, the bonding area between the active material layer in the battery and the composite current collector is small, resulting in low bonding force and easy material drop; (3) The conductive path is small, which increases the interface resistance between the active material and the metal layer of the composite current collector.

[0005] To this end, it is necessary to develop an improved composite current collector and a method for controlling its surface roughness, which can significantly improve the adhesion, conductivity and cycle stability of the battery electrode, thereby enhancing the overall performance of the battery. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides an improved composite current collector and a method for controlling its surface roughness. The improved composite current collector can optimize the surface roughness of the composite current collector by etching linear grooves on the surface of the metal layer, significantly improve the adhesion, conductivity and cycle stability of the battery pole piece, and thus enhance the overall performance of the battery; the surface roughness control method of the present invention uses a laser etching method to form linear grooves on the metal surface, which can improve control accuracy and reduce damage to the composite current collector, which is beneficial to improving the performance of the electrode pole piece, thereby improving the performance of the lithium-ion battery.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an improved composite current collector, comprising a thin film substrate and a metal layer disposed on at least one surface thereof; the surface of the metal layer is etched with linear grooves.

[0009] The improved composite current collector of the present invention can optimize the surface roughness of the composite current collector by etching linear grooves on the surface of the metal layer, significantly improve the adhesion, conductivity and cycle stability of the battery pole piece, and thus enhance the overall performance of the battery.

[0010] As a preferred technical solution of the present invention, at least one of the following (a)-(d) is satisfied:

[0011] (a) The width of the linear groove is 0.001-0.005 mm, for example, 0.001 mm, 0.002 mm, 0.003 mm, 0.004 mm or 0.005 mm.

[0012] (b) The depth of the linear groove accounts for 10-50% of the thickness of the metal layer, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc.; generally, the depth of the linear groove is 100-500nm, for example, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, etc.

[0013] (c) The spacing between two adjacent linear grooves is 0.04-0.08 mm, for example, 0.04 mm, 0.045 mm, 0.05 mm, 0.055 mm, 0.06 mm, 0.065 mm, 0.07 mm, 0.075 mm or 0.08 mm.

[0014] (d) The linear groove includes a wavy groove.

[0015] It should be noted that the linear grooves described in the present invention also include linear grooves of other shapes, such as simple straight line grooves, or even linear grooves formed by customer-customized patterns.

[0016] As a preferred technical solution of the present invention, the linear groove extends along the width direction of the metal layer, and the extension length of the linear groove accounts for 60-90% of the width of the metal layer, for example, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc.

[0017] It should be noted that if the extension length of the linear groove is less than 60% of the width of the metal layer, it will lead to material waste, large fluctuations in internal resistance, battery cycle dives and other problems, and it will not be able to control the roughness; and the extension length of the linear groove cannot exceed 90%, or even full-width etching, because the battery tab cutting area must be reserved.

[0018] As a preferred technical solution of the present invention, the metal layer is an aluminum metal coating, and the single-side thickness of the aluminum metal coating is 500-1000nm, for example, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm or 1000nm, etc.

[0019] Alternatively, the metal layer is an aluminum metal coating, and the single-side thickness of the aluminum metal coating is 500-2000nm, for example, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm or 2000nm, etc.

[0020] It should be noted that the common metal layer on the composite current collector is a copper metal plating layer or an aluminum metal plating layer, but other metal layers are also applicable, such as a nickel metal layer, a zinc metal layer, a copper-tin alloy layer, and the like.

[0021] As a preferred technical solution of the present invention, the film base layer includes any one or a combination of at least two of a polypropylene film base layer (PP film), a biaxially oriented polypropylene film base layer (BOPP film), a polyimide film base layer (PI film), a polyethylene terephthalate film base layer (PET film), and a polyvinyl chloride film base layer (PVC film).

[0022] And / or, the thickness of the film base layer is 4.5-8 μm, for example, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm or 8 μm, etc.

[0023] In a second aspect, the present invention provides a method for controlling the surface roughness of the improved composite current collector as described in the first aspect, the surface roughness control method comprising the following steps:

[0024] (1) Pre-etching treatment: prepare the composite current collector and perform masking on the non-etching area of ​​the metal layer;

[0025] (2) Laser etching: setting laser etching parameters according to the target value of surface roughness; fixing the composite current collector to be etched on the laser processing platform, turning on the laser to etch the metal layer to form linear grooves;

[0026] (3) Post-etching treatment: The etched metal layer is subjected to mask removal treatment and heat treatment to obtain an improved composite current collector.

[0027] The surface roughness control method of the present invention uses a laser etching method to form linear grooves on the metal surface, which can improve control accuracy and reduce damage to the composite current collector; if metal layers are respectively provided on the two surfaces of the thin film base layer and need to be etched to form linear grooves respectively, in the actual etching process, after single-sided etching is completed, the operation can be repeated to perform reverse etching, which will not be repeated here.

[0028] As a preferred technical solution of the present invention, in step (1), the masking process includes: coating a layer of masking material on the non-etching area of ​​the metal layer, and the masking material can be a photoresist or other types of masking materials.

[0029] As a preferred technical solution of the present invention, in step (2), the laser etching parameters include laser power, laser wavelength, scanning speed, and pulse width.

[0030] Preferably, the laser power is 5-60W, for example, 5W, 10W, 15W, 20W, 25W, 30W, 35W, 40W, 45W, 50W, 55W or 60W, etc. Furthermore, the laser power for copper metal coating is 10-60W, and the laser power for aluminum metal coating is 5-55W.

[0031] Preferably, the laser wavelength is 190-400 nm, for example, 190 nm, 200 nm, 230 nm, 250 nm, 280 nm, 300 nm, 330 nm, 350 nm, 370 nm or 400 nm.

[0032] Preferably, the scanning speed is 50-100 mm / s, for example, 50 mm / s, 60 mm / s, 70 mm / s, 80 mm / s, 90 mm / s or 100 mm / s.

[0033] Preferably, the pulse width is 10-50 nanoseconds, for example, 10 nanoseconds, 15 nanoseconds, 20 nanoseconds, 25 nanoseconds, 30 nanoseconds, 35 nanoseconds, 40 nanoseconds, 45 nanoseconds or 50 nanoseconds.

[0034] As a preferred technical solution of the present invention, during the etching process described in step (2), dust collection is performed to promptly remove metal particles and other pollutants generated by etching.

[0035] As a preferred technical solution of the present invention, in step (3), the heat treatment includes placing the etched composite current collector into an oven for drying.

[0036] And / or, the heat treatment temperature is 100-150°C, such as 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.

[0037] The surface roughness control method of the present invention includes pre-etching treatment, laser etching, and post-etching treatment performed in sequence. The focus is on creating a series of linear grooves with a width of 0.001-0.005 mm on the surface of the metal layer through thin film laser etching technology, with a spacing of 0.04-0.08 mm and a depth controlled within 100-500 nm. After single-sided etching is completed, reverse etching can be performed if required. Subsequently, the composite current collector after etching is first subjected to dust removal treatment and then subjected to heat treatment at 100-150°C to ensure structural stability.

[0038] Specifically, the surface roughness control method of the improved composite current collector of the present invention comprises:

[0039] (1) Pre-etching treatment: preparing a composite current collector, winding the composite current collector on a reel, unwinding it continuously with the aid of a guide roller, and performing a masking treatment on the non-etching area of ​​the metal layer; the masking treatment includes: coating a layer of masking material on the non-etching area of ​​the metal layer;

[0040] (2) Laser etching: according to the target value of surface roughness, the laser etching parameters are set; the laser etching parameters include laser power, laser wavelength, scanning speed, and pulse width; the laser power is 5-60W; the laser wavelength is 190-400nm; the scanning speed is 50-100mm / s; the pulse width is 10-50 nanoseconds; the composite current collector to be etched is fixed on the laser processing platform by continuous unwinding with the help of a guide roller, and the laser is turned on to etch the metal layer to form a linear groove; during the etching process, dust removal is carried out to promptly remove metal particles and other pollutants generated by etching;

[0041] (3) Post-etching treatment: The etched metal layer is continuously unwound by means of a guide roller, and the mask is removed, followed by heat treatment. The heat treatment includes placing the etched composite current collector in an oven for drying. The oven temperature is set to 100-150°C and the speed of the composite current collector is set to 5-20 m / min, so that the heat treatment time per meter of the composite current collector is 15-30 seconds, thereby obtaining an improved composite current collector.

[0042] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0043] (1) The improved composite current collector of the present invention can optimize the surface roughness of the composite current collector by etching linear grooves on the surface of the metal layer, significantly improve the adhesion, conductivity and cycle stability of the battery electrode, and thus enhance the overall performance of the battery;

[0044] (2) The surface roughness control method of the present invention uses a laser etching method to form linear grooves on the metal surface, which can improve control accuracy and reduce damage to the composite current collector. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 is a schematic diagram of laser etching in one embodiment of the present invention.

[0046] In the figure: 1-thin film base layer; 2-metal layer; 3-linear groove; 4-laser.

[0047] Figure 2 It is a broken line groove obtained by laser etching of the present invention.

[0048] Figure 3 The linear grooves are similar to fish scale patterns obtained by laser etching of the present invention. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0050] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:

[0051] The present invention provides an improved composite current collector, which comprises a substrate layer and a metal layer disposed on at least one surface thereof; the surface of the metal layer is etched with linear grooves;

[0052] Among them, the width of the linear groove is 0.001-0.005mm; the depth of the linear groove accounts for 10-50% of the thickness of the metal layer; the spacing between two adjacent linear grooves is 0.04-0.08mm; the linear groove includes a wavy groove; the linear groove extends along the width direction of the metal layer, and the extension length of the linear groove accounts for 60-90% of the width of the metal layer; the metal layer is a copper metal plating layer, and the single-side thickness of the copper metal plating layer is 500-1000nm; or, the metal layer is an aluminum metal plating layer, and the single-side thickness of the aluminum metal plating layer is 500-2000nm; the film base layer includes any one of a polypropylene film base layer, a polyimide film base layer, a polyethylene terephthalate film base layer, and a polyvinyl chloride film base layer, or a combination of at least two of them; the thickness of the film base layer is 4.5-8μm.

[0053] The present invention also provides an improved method for controlling the surface roughness of a composite current collector, the surface roughness control method comprising the following steps:

[0054] (1) Pre-etching treatment: The composite current collector is wound on a reel and unwound continuously with the help of a guide roller. A suitable composite current collector material (such as copper / aluminum) is selected and its surface is ensured to be clean and free of contamination. Masking is performed on the non-etching area of ​​the metal layer. The masking treatment can coat a layer of photoresist or other types of masking materials on the non-etching area of ​​the metal layer to protect the non-etching area.

[0055] (2) Laser etching: First, according to the target value of surface roughness, set the laser etching parameters; specifically, determine the pattern and size characteristics of the linear groove according to customer needs, convert the designed pattern and its size characteristics into a data format that can be recognized by the laser equipment, and load the generated data file into the control system of the laser etching machine; at the same time, the roughness value will also be determined according to the specific needs of the customer. The larger the roughness value, the greater the laser power; Figure 1 A schematic diagram of laser etching in one embodiment is shown, wherein the composite current collector is composed of a thin film substrate and metal layers disposed on both surfaces thereof; the linear grooves obtained by laser etching are wavy grooves; in addition, the linear grooves obtained by laser etching can also be as follows Figure 2 The broken line groove shown can also be Figure 3 Linear grooves resembling a fish scale pattern are shown;

[0056] The laser etching parameters include laser power, laser wavelength, scanning speed, and pulse width; the laser power is 5-60W; the laser power for copper metal coating is 10-60W, and the laser power for aluminum metal coating is 5-55W; the laser wavelength is 190-400nm; the scanning speed is 50-100mm / s; the pulse width is 10-50 nanoseconds;

[0057] Then, the composite current collector to be etched is placed accurately on the laser processing platform and fixed in position by continuous unwinding with the help of guide rollers. The sample position is ensured to be accurate through visual systems or other means. If necessary, fine-tuning is performed. The laser etching machine is started to irradiate the target area according to the preset path. The laser energy is used to etch a specific part of the material to form a linear groove. Moreover, during the etching process, the dust collection system is started to remove the generated metal particles and other pollutants in time to keep the working environment clean and prevent secondary pollution.

[0058] (3) Post-etching treatment: Continuously unwind with the help of guide rollers, and remove the mask of the etched metal layer. In the case of using additional coatings, dry and wet etching methods are required to peel them off to ensure a clean surface; the etched composite current collector material is placed in an oven for drying as a heat treatment, and the oven temperature is set to 100-150°C, and the speed of the composite current collector is 5-20m / min, so that the heat treatment time per meter of the composite current collector is 15-30 seconds. After the heat treatment is completed, the composite current collector is taken out and naturally cooled to room temperature to obtain an improved composite current collector.

[0059] (4) Quality inspection and appearance inspection: Use a microscope or other tools to observe whether the etching results meet the expected standards and check for defects, unevenness, and other problems.

[0060] Example 1

[0061] The present embodiment provides an improved composite current collector and a method for controlling its surface roughness. The improved composite current collector comprises a polypropylene film substrate and aluminum metal coatings are arranged on two surfaces thereof; the surfaces of the two aluminum metal coatings are both etched with the same linear grooves; wherein the thickness of the polypropylene film substrate is 6 μm; the linear grooves extend along the width direction of the metal layer, and the extension length of the linear grooves accounts for 70% of the width of the metal layer; the linear grooves are wavy grooves; the width of the linear grooves is 0.001 mm, the spacing between two adjacent linear grooves is 0.04 mm, the depth of the linear grooves is 100 nm, and the single-side thickness of the aluminum metal coating is 1000 nm, that is, the depth of the linear grooves accounts for 10% of the thickness of the aluminum metal coating;

[0062] The surface roughness control method comprises the following steps:

[0063] (1) Pre-etching treatment: The composite current collector is wound on a reel and unwound continuously with the help of a guide roller. A composite current collector material with aluminum coating on both sides is selected, and its surface is ensured to be clean and free of pollution. Masking treatment is performed on the non-etching area of ​​the aluminum metal coating. The masking treatment is to coat a layer of photoresist on the non-etching area of ​​the aluminum metal coating to protect the non-etching area.

[0064] (2) Laser etching: First, according to the pattern and dimensional features of the aforementioned linear grooves, the designed pattern and its dimensional features are converted into a data format that can be recognized by the laser equipment, and the generated data file is loaded into the control system of the laser etching machine; the laser etching parameters include laser power, laser wavelength, scanning speed, and pulse width; for the aluminum metal coating, the laser power is 30W; the laser wavelength is 250nm; the scanning speed is 80mm / s; and the pulse width is 30 nanoseconds;

[0065] Then, the composite current collector to be etched is accurately placed on the laser processing platform and fixed in position by means of continuous unwinding with the help of guide rollers. The sample position is ensured to be accurate through visual systems or other means. If necessary, fine-tuning is performed. The laser etching machine is started, and the target area is irradiated according to the preset path. The laser energy is used to etch a specific part of the material to form a linear groove. Moreover, during the etching process, the dust collection system is started to promptly remove the generated metal particles and other pollutants to keep the working environment clean and prevent secondary pollution. After the single-side etching is completed, the relevant operations are repeated to perform reverse etching.

[0066] (3) Post-etching treatment: Continuously unwind with the aid of guide rollers, and perform mask removal on the etched aluminum metal coating. In the case of using additional coatings, dry or wet etching methods are required to peel them off to ensure a clean surface. The etched composite current collector material is placed in an oven for drying as a heat treatment. The oven temperature is set to 150° C., and the speed of the composite current collector is set to 15 m / min, so that the heat treatment time per meter of the composite current collector is 20 seconds. After the heat treatment is completed, the composite current collector is taken out and naturally cooled to room temperature to obtain an improved composite current collector.

[0067] (4) Quality inspection and appearance inspection: Use a microscope or other tools to observe whether the etching results meet the expected standards and check for defects, unevenness, and other problems.

[0068] Example 2

[0069] The present embodiment provides an improved composite current collector and a method for controlling its surface roughness, wherein the improved composite current collector comprises a polypropylene film substrate and aluminum metal coatings respectively disposed on two surfaces thereof; the surfaces of the two aluminum metal coatings are both etched with the same linear grooves; wherein the thickness of the polypropylene film substrate is 6 μm; the linear grooves extend along the width direction of the metal layer, and the extension length of the linear grooves accounts for 70% of the width of the metal layer; the linear grooves are wavy grooves; the width of the linear grooves is 0.005 mm, the spacing between two adjacent linear grooves is 0.08 mm, the depth of the linear grooves is 500 nm, and the single-side thickness of the aluminum metal coating is 1000 nm, that is, the depth of the linear grooves accounts for 50% of the thickness of the aluminum metal coating;

[0070] The surface roughness control method comprises the following steps:

[0071] (1) Pre-etching treatment: The composite current collector is wound on a reel and unwound continuously with the help of a guide roller. A composite current collector material with aluminum coating on both sides is selected, and its surface is ensured to be clean and free of pollution. Masking treatment is performed on the non-etching area of ​​the aluminum metal coating. The masking treatment is to coat a layer of photoresist on the non-etching area of ​​the aluminum metal coating to protect the non-etching area.

[0072] (2) Laser etching: First, according to the pattern and dimensional features of the aforementioned linear grooves, the designed pattern and its dimensional features are converted into a data format that can be recognized by the laser equipment, and the generated data file is loaded into the control system of the laser etching machine; the laser etching parameters include laser power, laser wavelength, scanning speed, and pulse width; for the aluminum metal coating, the laser power is 60W; the laser wavelength is 250nm; the scanning speed is 80mm / s; and the pulse width is 50 nanoseconds;

[0073] Then, the composite current collector to be etched is accurately placed on the laser processing platform and fixed in position by means of continuous unwinding with the help of guide rollers. The sample position is ensured to be accurate through visual systems or other means. If necessary, fine-tuning is performed. The laser etching machine is started, and the target area is irradiated according to the preset path. The laser energy is used to etch a specific part of the material to form a linear groove. Moreover, during the etching process, the dust collection system is started to promptly remove the generated metal particles and other pollutants to keep the working environment clean and prevent secondary pollution. After the single-side etching is completed, the relevant operations are repeated to perform reverse etching.

[0074] (3) Post-etching treatment: Continuously unwind with the aid of guide rollers, and perform mask removal on the etched aluminum metal coating. In the case of using additional coatings, dry or wet etching methods are required to peel them off to ensure a clean surface. The etched composite current collector material is placed in an oven for drying as a heat treatment. The oven temperature is set to 150° C., and the speed of the composite current collector is set to 15 m / min, so that the heat treatment time per meter of the composite current collector is 20 seconds. After the heat treatment is completed, the composite current collector is taken out and naturally cooled to room temperature to obtain an improved composite current collector.

[0075] (4) Quality inspection and appearance inspection: Use a microscope or other tools to observe whether the etching results meet the expected standards and check for defects, unevenness, and other problems.

[0076] Example 3

[0077] This embodiment provides an improved composite current collector and a method for controlling the surface roughness thereof. Compared with Embodiment 2, the only difference is that: the depth of the linear groove is reduced to 400 nm, and the single-side thickness of the aluminum metal coating is 1000 nm, that is, the depth of the linear groove accounts for 40% of the thickness of the aluminum metal coating;

[0078] In the surface roughness control method, the laser power for the aluminum metal coating is reduced to 50W.

[0079] Example 4

[0080] This embodiment provides an improved composite current collector and a method for controlling its surface roughness. Compared with Embodiment 2, the only difference is that the spacing of the linear grooves is increased to 0.10 mm. In the surface roughness control method, the spacing of the laser scanning is adjusted accordingly, and other laser etching parameters remain unchanged.

[0081] Example 5

[0082] This embodiment provides an improved composite current collector and a method for controlling its surface roughness. Compared with Embodiment 2, the only difference is that the width of the linear groove is reduced to 0.003 mm; in the surface roughness control method, the laser scanning width of the laser etching is adjusted accordingly, and other laser etching parameters remain unchanged.

[0083] Comparative Example 1

[0084] This comparative example provides an ordinary composite current collector without any improvement on the metal layer, that is, the unimproved composite current collectors of Example 1 and Example 2 are used as comparative examples, specifically: the composite current collector includes a polypropylene film base layer and aluminum metal coatings respectively arranged on its two surfaces; wherein the thickness of the polypropylene film base layer is 6μm; and the single-side thickness of the aluminum metal coating is 1000nm.

[0085] Performance Test:

[0086] (1) After etching, the composite current collectors described in the above embodiment and the comparative example are tested for surface roughness, sheet resistance, tensile strength MD, and tensile strength TD;

[0087] Specifically, the surface roughness is detected by a non-contact optical profilometer, and the difference in optical path length is measured using the interference principle to determine the relevant physical quantities; the sheet resistance is tested according to "GB / T 22586-2018", with a test point spacing of 10 cm and the average value is taken; the tensile strength is tested according to "GBT 25255-2010", with 10 sample data items and the average value is taken.

[0088] (2) The composite current collectors described in the above embodiment and the comparative example were subjected to positive electrode active material homogenization, coating, and roller pressing in sequence, and the obtained positive electrode pole pieces were subjected to pole piece peeling force test. The specific test method was carried out in accordance with GBT 2792-2014, and the single-sided sample data amount was 3, and the average value was taken.

[0089] (3) The positive electrode sheets prepared above are assembled into button batteries, and a cycle test is performed. The specific test method is based on GBT 31484-2015. The obtained button batteries are subjected to a 1C charge and discharge cycle test, and the discharge capacity of each cycle is recorded. The capacity retention rate of each cycle is calculated according to the calculation formula: capacity retention rate = discharge capacity of a certain cycle / discharge capacity of the first cycle, and the number of cycles corresponding to the capacity retention rate dropping to 80% is recorded.

[0090] The specific test results of the performance test are summarized in Table 1.

[0091] Table 1

[0092]

[0093] It can be seen from Table 1 that:

[0094] (1) Compared with Comparative Example 1, Example 1 improves the surface roughness by laser etching linear grooves on the surface of the metal layer, which can not only ensure that the block resistance, tensile strength MD, and tensile strength TD meet the standards, but also increase the electrode peeling force by 45.8% and the number of cycles (capacity retention rate 80%) by 31.1%.

[0095] (2) Compared with Comparative Example 1, Example 2 significantly improves the surface roughness by laser etching linear grooves on the surface of the metal layer, which can not only ensure that the block resistance, tensile strength MD, and tensile strength TD meet the standards, but also increase the electrode peeling force by 58.3% and the number of cycles (capacity retention rate 80%) by 75.1%.

[0096] (3) Comparing Example 2 with Examples 3, 4, and 5, Example 3 reduces the surface roughness by reducing the depth of the linear grooves. Although the electrode peeling force is not significantly affected, the number of cycles (capacity retention rate 80%) is only increased by 18.4% compared with Comparative Example 1; Example 4 reduces the surface roughness by increasing the spacing of the linear grooves. Although the electrode peeling force is not significantly affected, the number of cycles (capacity retention rate 80%) is only increased by 10.4% compared with Comparative Example 1; Example 5 reduces the surface roughness by reducing the width of the linear grooves. Although the electrode peeling force is not significantly affected, the number of cycles (capacity retention rate 80%) is only increased by 1.6% compared with Comparative Example 1; Therefore, the surface roughness can be adjusted according to the specific needs of customers, and the control accuracy of the surface roughness can be improved.

[0097] In summary, the improved composite current collector described in the present invention can optimize the surface roughness of the composite current collector by etching linear grooves on the surface of the metal layer, significantly improve the adhesion, conductivity and cycle stability of the battery pole piece, and thus enhance the overall performance of the battery; experimental results show that compared with the current collector with uncontrolled surface roughness, the adhesion of the pole piece of the composite current collector with optimized roughness is improved by more than 45.8%, up to 62.5%, and the cycle stability is improved by more than 1.6%, up to 75.1%.

[0098] In the present invention, the composite current collector with optimized roughness has significantly enhanced electrode adhesion, reduced the probability of active material peeling, and improved the cycle stability of the battery; the increase in surface roughness helps to form more electron transmission paths, thereby improving the conductive network inside the battery and enhancing the overall conductivity; the optimization of the microstructure makes it easier for the electrolyte to penetrate into the electrode, promotes the uniform diffusion of lithium ions, and extends the service life of the battery; by precisely controlling the roughness, the problems of increased internal resistance and uneven distribution of active materials caused by excessive roughness are avoided, and the relationship between battery performance and cost is balanced.

[0099] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0100] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0101] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0102] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. An improved composite current collector, characterized in that: The improved composite current collector comprises a thin film base layer and a metal layer arranged on at least one surface of the thin film base layer; the surface of the metal layer is etched with linear grooves.

2. The improved composite current collector according to claim 1, characterized in that: Satisfy at least one of the following (a)-(d): (a) the width of the linear groove is 0.001-0.005 mm; (b) the depth of the linear groove accounts for 10-50% of the thickness of the metal layer; (c) The distance between two adjacent linear grooves is 0.04-0.08 mm; (d) The linear groove includes a wavy groove.

3. The improved composite current collector according to claim 1, characterized in that: The linear groove extends along the width direction of the metal layer, and the extension length of the linear groove accounts for 60-90% of the width of the metal layer.

4. The improved composite current collector according to claim 1, characterized in that: The metal layer is an aluminum metal coating, and the single-side thickness of the aluminum metal coating is 500-1000nm; Alternatively, the metal layer is an aluminum metal coating, and the single-side thickness of the aluminum metal coating is 500-2000 nm.

5. The improved composite current collector according to claim 1, characterized in that: The film base layer includes any one of a polypropylene film base layer, a biaxially oriented polypropylene film base layer, a polyimide film base layer, a polyethylene terephthalate film base layer, and a polyvinyl chloride film base layer, or a combination of at least two thereof; And / or, the thickness of the film base layer is 4.5-8 μm.

6. A method for controlling the surface roughness of the improved composite current collector according to any one of claims 1 to 5, characterized in that: The surface roughness control method comprises the following steps: (1) Pre-etching treatment: prepare the composite current collector and perform masking on the non-etching area of ​​the metal layer; (2) Laser etching: setting laser etching parameters according to the target value of surface roughness; fixing the composite current collector to be etched on the laser processing platform, turning on the laser to etch the metal layer to form linear grooves; (3) Post-etching treatment: The etched metal layer is subjected to mask removal treatment and heat treatment to obtain an improved composite current collector.

7. The surface roughness control method according to claim 6, characterized in that: In step (1), the masking process includes: coating a layer of masking material on the non-etching area of ​​the metal layer.

8. The surface roughness control method according to claim 6, characterized in that: In step (2), the laser etching parameters include laser power, laser wavelength, scanning speed, and pulse width; the laser power is 5-60W; the laser wavelength is 190-400nm; the scanning speed is 50-100mm / s; and the pulse width is 10-50 nanoseconds.

9. The surface roughness control method according to claim 6, characterized in that: During the etching process of step (2), dust collection is performed to promptly remove metal particles and other pollutants generated by etching.

10. The surface roughness control method according to claim 6, characterized in that: In step (3), the heat treatment includes placing the etched composite current collector in an oven for drying; And / or, the heat treatment temperature is 100-150°C.